1991
DOI: 10.3402/polar.v10i2.6774
|View full text |Cite
|
Sign up to set email alerts
|

Oil-weathering behavior in Arctic environments

Abstract: Oil-weathering processes in ice-free subarctic and Arctic waters include spreading, evaporatlon. dissolution, dispersion of whole-oil droplets into the water column, photochemical oxidation. water-in-oil emulsification, microbial degradation, adsorption onto suspended particulate material, ingestion by organisms. sinking. and sedimentation. While many of these processes also are important factors in ice-covered waters, the various forms of sea ice (depending on the active state of ice growth, extent of coverag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 14 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…Increasing periods of open water in the Arctic have expanded shipping activities and opportunities for oil and gas exploration and production, resulting in greater potential for oil spills (Corbett et al, 2010;Gautier et al, 2009;Nevalainen et al, 2017;Noble et al, 2013). Exposure of Artic species in the aquatic environment to petroleum hydrocarbons may be compounded by slower hydrocarbon degradation (Brakstad and Bonaunet, 2006;Venosa and Holder, 2007) and volatilization of toxic fractions at low Arctic temperatures (Perkins et al, 2005), and oil dynamics in and under sea ice (Brandvik and Faksness, 2009;Payne et al, 1991;Seelye, 1979). Additionally, because of the limited complexity of Arctic food webs (e.g., five trophic levels; Borgå et al, 2004;Bradstreet and Cross, 1982;Hobson and Welch, 1992;Welch et al, 1992), impacts on key species such as Arctic cod Boreogadus saida and lower trophic level invertebrates may result in disruptions of energy transfer to higher trophic level vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing periods of open water in the Arctic have expanded shipping activities and opportunities for oil and gas exploration and production, resulting in greater potential for oil spills (Corbett et al, 2010;Gautier et al, 2009;Nevalainen et al, 2017;Noble et al, 2013). Exposure of Artic species in the aquatic environment to petroleum hydrocarbons may be compounded by slower hydrocarbon degradation (Brakstad and Bonaunet, 2006;Venosa and Holder, 2007) and volatilization of toxic fractions at low Arctic temperatures (Perkins et al, 2005), and oil dynamics in and under sea ice (Brandvik and Faksness, 2009;Payne et al, 1991;Seelye, 1979). Additionally, because of the limited complexity of Arctic food webs (e.g., five trophic levels; Borgå et al, 2004;Bradstreet and Cross, 1982;Hobson and Welch, 1992;Welch et al, 1992), impacts on key species such as Arctic cod Boreogadus saida and lower trophic level invertebrates may result in disruptions of energy transfer to higher trophic level vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…n-alkanes lighter than n-C 11 can be lost within 9 days in a surface spill (Payne et al, 1991). In some cases, elevated salinity can increase evaporation rates and decrease dissolution (Oyewo, 1988).…”
Section: Assessing Petroleum Weathering With Chromatogramsmentioning
confidence: 99%
“…However, research and response experiences in sub-arctic and arctic areas have shown that low temperatures and ice can also enhance spill response and reduce environmental impacts under certain conditions (Shell et al 1983;Payne et al, 1991;Dickins and Buist 1999;Dickins 2004;Alaska Clean Seas 2005;SINTEF 2006;Allen and Dickins 2007;SL Ross 2007;;ExxonMobil Research and Engineering 2008). However, research and response experiences in sub-arctic and arctic areas have shown that low temperatures and ice can also enhance spill response and reduce environmental impacts under certain conditions (Shell et al 1983;Payne et al, 1991;Dickins and Buist 1999;Dickins 2004;Alaska Clean Seas 2005;SINTEF 2006;Allen and Dickins 2007;SL Ross 2007;;ExxonMobil Research and Engineering 2008).…”
Section: Oil Spill Planning and Response In Arctic And Cold Water Envmentioning
confidence: 99%